A companion to ancient Near Eastern art - Gunter, Ann Clyburn 1951- (Hoboken Wiley Blackwell, 2018)
Evans 19 Palaces and Elite Houses 457; Andreas Schachner 20 Rock Reliefs and Landscape Monuments 483; Ömür Harmansa̧ h 21 Reconstructing Artistic Environments 507; Mehmet‐Ali Ataç PART IV Interactions with Neighboring Regions and Artistic Traditions 531 22 The Ancient Near East and Egypt 533; Betsy M. Bryan 23 The Ancient Near East and the Bronze Age Aegean 565; Marian H. Feldman 24 Near Eastern Art in the Iron Age Mediterranean 585; James Whitley PART V Intersections with Archaeology, Collecting, and Cultural Heritage 613 25 Archaeology and the Art of the Ancient Near East 615; D. T. Potts 26 Cultural Heritage across the Middle East, Ancient and Modern 637; Geoff Emberling and Katharyn Hanson Index 661
Green 9 Semiotics, Reception Theory, and Poststructuralism 209; Marlies Heinz PART II Critical Terms and Concepts 231 10 Representation 233; Dominik Bonatz and Marlies Heinz 11 Narrative 261; Paul Collins 12 Ideology 283; Beate Pongratz‐Leisten 13 Ritual 309; Carolyn Nakamura 14 Agency 333; Sophy Downes; ; 15 Aesthetics 359; Gebhard J. Selz PART III Materials, Media, and Artistic Environments 383 16 Statuary and Reliefs 385; Claudia E. Suter 17 Glyptic 411; Adelheid Otto 18 Religious Architecture 433; Jean M
Notes on Contributors ix Preface xiii Acknowledgments xvii Abbreviations xix 1 The “Art” of the “Ancient Near East” 1; Ann C. Gunter PART I Approaches and Methods of Analysis and Interpretation 23 2 Art and Material Culture 25; David Wengrow 3 Meaning and Interpretation 49; Astrid Nunn 4 Style 75; Margaret Cool Root 5 Connoisseurship and Classification 103; Eleonora Pappalardo 6 Visual Culture 129; Sarah B. Graff 7 Technical Examination and Material Analysis 153; Deborah Schorsch 8 Gender and Sexuality 179; John D. M
Includes bibliographical references and index. - Print version record and CIP data provided by publisher; resource not viewed
Online-Ausg.
Keywords: Art, Ancient -- Middle East -- Middle East; Art, Middle Eastern; Art, Ancient -- Middle East; Art, Ancient; Middle East; ART ; History ; General; Art moyen-oriental; Art, Middle Eastern; Electronic books